ERROR ANALYSIS OF DERIVATIONAL AFFIXES ON ELEVENTH GRADE STUDENTS IN WRITING NARRATIVE AND ANALYTICAL EXPOSITION TEXT - Nurul Fadhilah Lubis and Busmin Gurning (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2016)
This research deals with the derivational affixes errors in writing narrative andanalytical exposition text by eleventh grade students. This research uses aqualitative design in which the data are taken from the sentences of texts. Dulay’stheory is applied to analyze students’ error in writing and divided each error intotypes. The researcher applies random technique to get a representative sample.The source of data in this study is Eleventh Grade (XI) students of SMA SwastaMa’had Muhammad Saman, 30 students are choosen as the sample. The data ofthis study is taken from the students’ writing narrative and analytical expositiontext. The analysis found that there are four classification of errors occured instudents’ writing; they are omision 10 cases, addition 4 cases, misformation 11cases and misorder 13 cases. Besides, the class changing is the most derivationalerrors that contributes 33 cases (86.8%) then followed by class maintainingderivational that contributes 5 cases (13,2%). In this study also found that thecauses of errors are intralingual and interlingual transfer. It is hoped that the resultof this research is useful for everyone who wants to study or make a similarresaerch about affixation errors.